(untitled) (International Journal of Built Environment and Sustainability, 2016)
The common causes of construction collapse are mainly design, materials, accidents, the elements, workmanship and supervision. Regarding the increasingly frequent incidents in the Lagos Metropolis, published findings of researchers have not been markedly different. This paper argues that beyond the technical issues already raised, there are important factors yet to be investigated, which may be classified as being non-technical in nature, but constitute hindrances not only to the capacity of the supervising agency, the Lagos State Building Control Agency to perform its functions, but more importantly, to the effective execution of building control generally. The study reviews earlier findings, the practice and challenges of building control in the Lagos Metropolis before identifying and discussing these other factors. The findings are that the building control function is inappropriately assigned to the state government, rather than the local governments, and that the state bureaucracy cannot effectively execute building control because of poor capacity and practices. The most important implication of this research is that, by drawing attention to issues which have hitherto been unconsidered, it brings to notice the need to ascertain pragmatically which tier of government is better suited to execute building control and offer the required capacity and organizational effectiveness.